Responses of the African and American Equatorial Ionization Anomaly (EIA) to 2014 Arctic SSW Events. Issue 11 (2nd November 2021) - Idolor, O. R.; Akala, A. O.; Bolaji, O. S.
Abstract: Aside from the influence of forcing from above on the ionosphere during space weather, forcing from below also have significant influence on the ionosphere. This study investigates responses of the equatorial ionization anomaly (EIA) in the African and American longitudinal sectors to the combined effects of 2014 Sudden Stratospheric Warming (SSW) events and geomagnetic storms that coexisted with them. The study locations cover ±40° geomagnetic latitudes in both sectors. A multiinstrument approach with models was adopted. During the SSW events, a hemispherical asymmetry in TEC distribution was observed, with higher plasma ionization in the Northern Hemisphere (NH). Generally, in both sectors, EIA crests locations shifted to higher latitudes during peak phases of SSW, except in the SH of the African sector, where crests locations shifted to lower latitudes. Reversal of stratospheric zonal mean wind direction supported reversed fountain effect. TEC responded positively to SSW peak phases and daytime or nighttime orientation of Prompt Penetration Electric Field (PPEF) and PPEF strength played major role on TEC responses to storms. PPEF values were generally weak, but comparatively higher in the American sector. TEC were predominant in the American sector than the African sector due to the comparative higher electrodynamics over the American sector. EIA crests were generally located at higher latitudes on the days of SSW peaks than on the days of geomagnetic storms, except in the NH of the American sector. In both sectors, geomagnetic storms modified ionospheric irregularities by weakening or enhancing them, while the major SSW event weakened irregularities. Plain Language Summary: We investigated the responses of the EIA in the African and American sectors to the combined effects of 2014 SSW events and the geomagnetic storms that coexisted with them. We chose the study locations to cover ±40° geomagnetic latitudes in both sectors. We adopted a multiinstrument approach with models. Our results showed that the EIA crests locations in the African sector shifted from lower latitudes on pre‐SSW days to higher latitudes on minor SSW peak days in the NH. In the SH, these crests locations shifted from higher latitudes on pre‐SSW days to lower latitudes on SSW peak days, except on the day of the major SSW peak when the crest location shifted from lower latitude on pre‐SSW days to higher latitude on SSW peak days. In the American sector, EIA crest locations shifted from lower latitudes on pre‐SSW days to higher latitudes on the SSW peak days in both hemispheres. Reversal of stratospheric zonal mean wind direction supported reversed fountain effect. Both the strength and orientation of PPEF played major roles on TEC responses to storms. Furthermore, occurrence of geomagnetic storm modified ionospheric irregularities. Weakening of irregularities was noticed during days of the major warming in the American sector. Key Points: EIA crests locations expanded during 2014 arctic SSW event and the event weakened ionospheric irregularities Reversal of stratospheric zonal mean wind direction supported reversed fountain effect Ionospheric electrodynamics was higher over the American sector than over the African sector